اقبال اور نژادِ نو:تحقیق و تجزیہ: Iqbal and New generation: Research and Analysis - Naqvi, Dr. Rizwana; Mehmood, Dr.Qaiser (Tashkeel e Jadeed, 2025)
Allama Iqbal is a great poet of Urdu and Persian literature.He had a great love for children.He knew that today’s children are the architects of tomorrow,so it is most important that they should be educated and trained in a better way and adoraned with the jewels of education.Allama Iqbal wrote very interesting, meaningful, effective, simple and instructive poems to instill good habbits in children and to train them better,many lessons and advice have been explained to children in his poetry in a very effective manner. In these poems iqbal teaches children moral values and how to live a bettr and useful life towards self and towards world, after reading his poetry children become optimistic, enthusiasti and when they poses these qualities they can lead the world, although Iqbal wrote less about children as compare to youth but his poems have a rich message and impacts.This article sheds the light on the facts,effects, usefulness and value of Iqbal’s poetry for New Generation.